THE INTEGRATED TERRITORIAL DEVELOPMENT TOOLS - A KEY COMPONENT OF THE EUROPEAN COHESION POLICY - Stoyanova, Mariela; Pavlova-Banova, Mariyana; Aleksandrova, Aleksandrina (Revista Inclusiones, 2023)
The publication aims to study the implementation of the instruments for integrated territorial development in the EU in the context of the Cohesion policy. The research framework covers a literature review and a critical comment on the concept of the idea of introducing an integrated territorial approach to achieve convergence, emphasizing the applicable three territorial development approaches in the Member States: Community-Led Local Development, Sustainable Urban Development and Integrated territorial investments. Key conclusions are drawn, which are the result of an analysis of secondary data on the financial performance of the territorial development approaches for the 2014-2020 planning period. The authors focus on the specific challenges that the EU faces in measuring the effectiveness of the integrated territorial instruments in the new programming period. This study also puts an emphasis on the need for the development of a new generation of territorial impact assessment methods, instruments and indicators for measuring combined actions capable of evaluating the integration of EU. Based on an expert assessment of interrelationships, specific recommendations are made to over-come the challenges of implementing and monitoring of the instruments for integrated territorial development during the new programming period.